Population aging and migration - history and UN forecasts in the EU-28 and its east and south near neighborhood - one century perspective 1950-2050 - Mihajlo Michael Jakovljevic; Yael Netz; Sandra C. Buttigieg; Roza Adany; Ulrich Laaser; Mirjana Varjacic (BMC, 2018)
Abstract Background There is a gap in knowledge on long term pace of population aging acceleration and related net-migration rate changes in WHO European Region and its adjacent MENA countries. We decided to compare European Union (EU-28) region with the EU Near Neighborhood Policy Region East and EU Near Neighborhood Policy Region South in terms of these two essential features of third demographic transition. One century long perspective dating back to both historical data and towards reliable future forecasts was observed. Methods United Nation's Department of Economic and Social Affairs estimates on indicators of population aging and migration were observed. Time horizon adopted was 1950-2050. Targeted 44 countries belong to either one of three regions named by EU diplomacy as: European Union or EU-28, EU Near Neighborhood Policy Region East (ENP East) and EU Near Neighborhood Policy Region South (ENP South). Results European Union region currently experiences most advanced stage of demographic aging. The latter one is the ENP East region dominated by Slavic nations whose fertility decline continues since the USSR Era back in late 1980s. ENP South region dominated by Arab League nations remains rather young compared to their northern counterparts. However, as the Third Demographic Transition is inevitably coming to these societies they remain the spring of youth and positive net emigration rate. Probably the most prominent change will be the extreme fall of total fertility rate (children per woman) in ENP South countries (dominantly Arab League) from 6.72 back in 1950 to medium-scenario forecasted 2.10 in 2050. In the same time net number of migrants in the EU28 (both sexes combined) will grow from − 91,000 in 1950 to + 394,000 in 2050. Conclusions Long term migration from Eastern Europe westwards and from MENA region northwards is historically present for many decades dating back deep into the Cold War Era. Contemporary large-scale migrations outsourcing from Arab League nations towards rich European Protestant North is probably the peak of an iceberg in long migration routes history. However, in the decades to come acceleration of aging is likely to question sustainability of such movements of people.